Fast facts for developing a nursing academic portfolio : what you really need to know in a nutshell - Wittmann-Price, Ruth A. (Springer Pub. Co., 2012)
Using the Fast Facts style of concise, easy-to-access information, this book is the only comprehensive guide to creating an outstanding professional academic portfolio for entry into, and promotion and tenure within, an academic nursing setting. It is designed for recent nursing graduates who want to teach, faculty who need to polish their academic portfolio and individuals already established in academia who seek promotion or tenure. The book provides clear guidelines on what to include in a professional portfolio, and elements to highlight when seeking work in a specific discipline or academic role. It describes pitfalls to be avoided and how to ensure effective coverage of teaching, scholarship, and service, as well as addresses the differences between systems and policies of academia versus those of community college nursing programs and diploma schools of nursing. This guide also helps prepare nurses for the rigors of promotion and tenure by clarifying what to expect and how candidates are evaluated. Numerous examples illustrate actual professional faculty experiences and include personal statements written by successful nurse educators.